An assessment of IFPRI’S work in Ethiopia 1995–2010: Ideology, influence, and idiosyncrasy - Renkow, Mitch; Slade, Roger (International Food Policy Research Institute, 2013)
This study provides an assessment of the impact of the International Food Policy Research Institute (IFPRI)’s work in Ethiopia during the period of 1995–2010. From 1995 to 2004, nearly all of IFPRI’s Ethiopia work was undertaken by Washington-based research teams working on specific themes under various “global research programs” (GRPs). In each case, Ethiopia represented one of several case studies in a larger multicountry study. The international public goods (IPGs) generated in this way included peer-reviewed publications; collaborative research with both domestic and international researchers; and the building of national capacity for policy research.